2006
DOI: 10.1021/bi052026e
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Specific Membrane Activity of Human β-Defensin-3

Abstract: Defensins represent a major component of innate host defense against bacteria, fungi, and enveloped viruses. One potent defensin found, e.g., in epithelia, is the polycationic human beta-defensin-3 (hBD3). We investigated the role of the lipid matrix composition, and in particular the presence of negatively charged lipopolysaccharides (LPS) from sensitive (Escherichia coli, Salmonella enterica serovar Minnesota) or resistant (Proteus mirabilis) Gram-negative bacteria or of the zwitterionic phospholipids of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…6). Similar properties of HBD2 and HBD3 were previously reported because they disrupted bacterial cell wall and lipid bilayers (41)(42)(43)(44). In case of HIV-1, HBD3 also conferred its antiviral activity by down-regulating cell surface expression of HIV-1 receptor CXCR4 (81).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…6). Similar properties of HBD2 and HBD3 were previously reported because they disrupted bacterial cell wall and lipid bilayers (41)(42)(43)(44). In case of HIV-1, HBD3 also conferred its antiviral activity by down-regulating cell surface expression of HIV-1 receptor CXCR4 (81).…”
Section: Discussionsupporting
confidence: 76%
“…HBDs are known to play an important role in innate immune response by virtue of their potent antimicrobial activity against Gram-negative and Gram-positive bacteria. HBDs are highly cationic, and it is suggested that the amphipathic character of HBDs is responsible for their antimicrobial activity, because they can interact with the bacterial membrane (by interacting with the negatively charged phospholipids of the bacterial membrane) leading to permeabilization (disruption of cell wall) and release of cellular contents (11)(12)(13)(41)(42)(43)(44). The three well established HBDs belonging to the ␤-defensin family of polypeptides are HBD1, HBD2, and HBD3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBD1 to -3). N-terminal regions of defensins are often more aliphatic, and since helices are a frequent structural motif in antimicrobial peptides, it is likely that this is the region of the peptide that directs membrane insertion and disruption (37). It is also interesting to note that D14ip1 contains within it a stretch of eight amino acids (GGRAAVLN), which are identical to the XT4 peptide fragment of an antimicrobial peptide isolated from the skin secretions of the diploid frog (38).…”
Section: Antimicrobial Functionmentioning
confidence: 99%
“…They kill gram-negative bacteria, gram-positive bacteria, and fungi and inhibit some viral infections (18,21,25,28,48); chemoattract monocytes, macrophages, CD45 RA ϩ /CD4 ϩ T lymphocytes, mast cells, and immature dendritic cells (10,21,62); enhance antigen-specific immune responses (9,38); and even possibly regulate pigmentation and body weight via modulation of Mc1r and Mc4r (1). Defensins also bind to bacterial membranes (7,17) and lipopolysaccharides (17,39) and neutralize select bacterial toxins (23,31,32). Binding of human neutrophil peptide ␣-defensins (HNPs) and human ␤-defensins (HBDs) to these materials may facilitate receptor-mediated internalization of microbial antigens to immature dendritic cells (61) or attenuate antigen-induced proinflammatory cytokine responses (44).…”
mentioning
confidence: 99%